APLIKASI MULTIMEDIA BERHITUNG CEPAT UNTUK ANAK SEKOLAH DASAR - Ronaldo, Deddy; Ratu, Triana (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2015)
Elementary school student needs to learn tips and tricks in calculation. The book "Speed Mathematics: Secret Skills for Quick Calculation." gives tips and tricks to help student learn the basics of the calculation quickly. Currently, the elementary school students need a facility to help student learn interactively.Multimedia application can facilitate the needs of children to learn interactilvely. The application can be used anywhere and anytime. This study tries to visualize the book Speed Mathematics: Secret Skills for Quick Calculation" to be a learning tool through a multimedia application for elementary school student. The methodology that used to develop the application is a multimedia methodology of Luther.The multimedia application that has built in this research provides an interactive material that helps students understand the basic concepts of calculation. For further development, the application can be developed by adding material contents and animations